Sosialisasi Literasi Keuangan Digital Melalui Webinar untuk Meningkatkan Pemahaman Mahasiswa Terhadap Pinjaman Online - Kuntadi, Yahya Agung; Satyawati, Endang; Asmarawati, Sandra Galuh (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The development of financial technology (fintech), especially online loans (pinjol), has provided easy access to financial services, but also poses risks, especially for students who are vulnerable to the trap of illegal pinjol. This study aims to analyze the effectiveness of digital financial literacy socialization activities through the "Pinjol Goes to Campus" webinar in increasing students' understanding and critical attitudes towards online loans. The activity was carried out online on May 21, 2024, presenting experienced speakers from the banking industry and academics. A total of 93 students from Universitas Kristen Teknologi Solo and other universities participated in the webinar. The research method used a quantitative approach with a pre-test and post-test design, as well as qualitative analysis of participant feedback. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. The results showed a significant increase in participants' understanding of 14 of the 15 statements analyzed (p-value <0.05), with an average increase in scores ranging from 0.14 to 1.11. Qualitative analysis showed a positive response from participants to the quality of the material, the professionalism of the speakers, and the relevance of the content. The webinar was proven to be effective in increasing students' digital financial literacy. This activity can be a model of educational intervention to prevent students from getting caught up in detrimental online loan practices.